Lessness:Randomness, Consciousness and Meaning - HAAHR, MADS (Curtin University of Technology, 2002)
Lessness is a prose piece by Samuel Beckett in which he used random permutation to order sentences. Like interactive artworks, the piece is experienced as a process that depends upon the participant?s attempts to comprehend and create meaning. Although Lessness is linear prose, its orderly disorder sets up a non-linear reading process in which contradictory perspectives are viewed simultaneously. The piece comprises two of the approximately 8.3 x1081 possible orderings of Beckett?s 60 sentences. The authors have developed a web site that generates versions of Lessness, exploring the effects of the capabilities of computing in the creation and exploration of art.
PUBLISHED
Keywords: Chaos; Randomness; Samuel Beckett; postmodern fiction; permutation; consciousness